Penegakan Hukum terhadap Admin Judi Online berdasarkan Pasal 27 Ayat (2) Undang-Undang Republik Indonesia No. 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang No. 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Anzward, Bruce; Rayung Wulan, Sri Endang; Utami, Nihaya Lila (Universitas Ekasakti, 2023)
Indonesia as a developing country continues to strive to advance its resources, especially technology in the field of communication, becoming one of the rapidly growing and accepted fields in human life. convenience for their lives, especially with the internet media in it. The internet not only has a positive impact but also has a negative impact. One of the negative impacts that is happening and is currently rife among the public is online gambling games. The problem approach used in this study is a normative juridical approach. The approach taken is an approach on matters of a juridical nature which uses legal materials such as laws, books, related journals. The ITE Law in Article 45 paragraph (2) and also Article 27 paragraph (2) will only serve as objects used to ensnare gambling which has been explained by Article 303 of the Criminal Code in electronic media. So that the point of reading the sentence regarding gambling is in Article 303 of the Criminal Code. It is not enough to carry out the activities, but all of them must be supported by the inner attitude of the perpetrators themselves. Where in Article 303 of the Criminal Code it is explained that the inner attitude of the perpetrator must be